The varieties of religious experience = pengalaman-pengalaman religius / William James ; alih bahasa Luthfi Anshari ; penyunting Bunga Matahari. - JAMES, William; Luthfi Anshari (IRCISoD, 2015)
508 hlm. ; 24 cm [3 eks.]